The Challenges in Paraphrasing Among English Language Students - Analyn S. Clarin; Sheen S. Serohijos; Larry L. Sumaylo; Genelyn R. Baluyos (EduLine: Journal of Education and Learning Innovation, 2023)
Paraphrasing is the most challenging part of academic writing. This study explored the challenges encountered by English language students in one of the Higher Education Institutions in Ozamiz City during the second semester of the school year 2021-2022. This study utilized phenomenological research design. The participants were 14 third-year English major students and were chosen using purposive sampling. A semi-structured interview was used based on the interview guide to gather the needed information. Moustakas's transcendental phenomenology was used in analyzing the participants’ responses. Students faced different challenges when paraphrasing texts and results revealed four themes: 1.) lack of vocabulary skills, 2.) inaccuracy of paraphrasing tools, 3.) poor reading comprehension skills, and 4.) copying someone else's work. Researchers suggest that teachers can put much effort into helping students comprehend how to paraphrase English texts. Also, the students have to be aware of how crucial paraphrasing is in writing.